Choosing a Design Science Research Methodology - Venable, John; Pries-Heje, J.; Baskerville, Richard (2017)
Design Science Research (DSR) is a popular new research approach and paradigm, for which a number of research methodologies have been developed. One of the challenges facing researchers wanting to apply this new approach is the choice of research methodology. In this paper we give an account of six DSR methodologies and we compare them using a Design Science Research Methodology Comparison Framework that we adapted from an existing Information Systems Development Methodology Comparison Framework. Based on the outcomes of the comparison, we develop a set of technological rules that forms a contingency-based framework to support Design Science Researchers in choosing an appropriate and well-suited DSR methodology, depending on the contingencies of the situation at hand.